Feasibility Study for Investment Decision in Silica Sand Mining Through Comparative Analysis of New Machine Purchase, Machine Refurbishment, and Joint Operation - Fachrezi, Muhammad Ghifari (Green Publisher Indonesia, 2025)
This study evaluates the feasibility of three investment alternatives for PT Naga Mas Sulawesi in the development of silica sand mining operations: the purchase of new machinery, the refurbishment of existing machinery, and operational cooperation. The main objective is to identify investment strategies that provide the best economic value by considering the financial performance and risk profile of each alternative. The analysis was conducted using PESTEL and VRIO frameworks to assess the company's external environment and internal capabilities, as well as the Discounted Cash Flow method with Net Present Value, Profitability Index, Payback Period, and Internal Rate of Return indicators to evaluate financial feasibility. Risk assessments were conducted using a risk matrix that identifies operational, financial, regulatory, and environmental exposures. The results show that the New Machine scenario provides the highest financial performance, with an NPV of IDR 2.15 trillion, a Profitability Index of 233.23, an IRR of 71%, and a Payback Period of 1.67 years, even though it entails greater operational risks. The Machine Refurbishment scenario generates moderate profits with medium-to-high risk, while the Joint Operation scenario offers stable royalty income with low risk but no operational control. Overall, the New Machine scenario is the most optimal choice, considering financial and risk aspects. Recommendations include strengthening operational planning, cost control, preventive maintenance, regulatory compliance, and long-term contract agreements to enhance competitiveness and long-term sustainability.